The Influence of Customer Perceptions, Service Features, and Security on Mobile Banking Customer Satisfaction at Indonesian Sharia Banks in Malang City - Muhammad Rafi Iriawan; Ulfi Kartika Oktaviana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of customer perception, service features, and security on mobile banking customer satisfaction at Bank Syariah Indonesia in Malang City. Along with the increasing use of digital banking services, understanding the factors that affect customer satisfaction is important for banks to improve service quality. This study uses a quantitative approach with multiple linear regression analysis methods. Data was collected through the distribution of questionnaires to Bank Syariah Indonesia mobile banking users in Malang City. The results of the analysis show that customer perception, service features, and security affect customer satisfaction. A good perception of the bank's services increases customer trust and convenience, complete and easy-to-use service features contribute to a better user experience, while guaranteed security is a key factor in maintaining customer loyalty. The results of this research can be a reference for Bank Syariah Indonesia in improving mobile banking services by paying attention to customer perception aspects, developing more innovative features, and improving security systems. This research can also be a reference for future research related to the satisfaction of users of digital banking services.